Electricity load forecasting based on artificial intelligence techniques [electronic resource] - Majid Joshani, 1982- (2010)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2010